Shakespeare in succession : translation and time - Saenger, Michael; Costola, Sergio (McGill-Queen's University Press, 2023)
"An edited collection, focused on ideas of temporality, language, and translation in relation to Shakespeare. Originating in a seminar at the European Shakespeare Research Association, this anthology brings together translators and theatrical practitioners writing about their own work, as well as scholars of translation discussing how Shakespeare read previous originals, and how subsequent interpreters have created versions of Shakespeare that bridge cultures, times, and artistic effects. The first half of the volume includes authors who have recently translated Shakespeare into another language, and also those who have translated Shakespeare into a more theatrical sense, moving the plays into modern performance spaces. These essays are largely dependent on the authors' personal work, so they are not written in the style of academic essays. The second half of the book, on the other hand, is written in the common mode of academic research, as is the introduction. The essays are unified by an interest in the nuances of localities and dialect, as well as a focus on the ways in which a sense of place and time is generated, or at least invoked, as part of the wide scope of creativity that can be linked to the idea of translation."--